An Extended PD-L2 Cytoplasmic Domain Results From Alternative Splicing in NSCLC Cells. Issue 9 (30th November 2022) - Dietz, Lisa Loksø; Furman, Natasja Toft; Larsen, Trine Vilsbøll; Daugaard, Tina Fuglsang; Thomsen, Emil Aagaard; Keller, Johanne Lade; Aagaard, Lars; Sorensen, Boe Sandahl; Nielsen, Anders Lade
Abstract : Antibody–based immunotherapy targeting the interaction between programmed cell death 1 (PD-1) and its ligand PD-L1 has shown impressive clinical outcomes in various cancer types, including nonsmall cell lung cancer (NSCLC). However, regulatory mechanisms in this immune checkpoint pathway still needs clarification. PD-L2 is structurally homologous to PD-L1 and is a second PD-1 ligand. Alternative mRNA splicing from the CD274 and PDCD1LG2 genes holds the potential to generate PD-L1 and PD-L2 isoforms, respectively, with novel functionality in regulation of the PD-1 immune checkpoint pathway. Here, we describe alternative splicing in NSCLC cells potentially generating eight different PD-L2 isoforms from the PDCD1LG2 gene. Extension of exon 6 by four nucleotides is the most prominent alternative splicing event and results in PD-L2 isoform V with a cytoplasmic domain containing a 10 amino acid extension. On average 13% of the PDCD1LG2 transcripts in NSCLC cell lines and 22% of the transcripts in NSCLC tumor biopsies encode PD-L2 isoform V. PD-L2 isoform V localizes to the cell surface membrane but less efficiently than the canonical PD-L2 isoform I. The cytoplasmic domains of PD-1 ligands can affect immune checkpoint pathways by conferring membrane localization and protein stability and thereby represent alternative targets for immunotherapy. In addition, cytoplasmic domains are involved in intracellular signalling cascades in cancer cells. The presented observations of different cytoplasmic domains of PD-L2 will be important in the future delineation of the PD-1 immune checkpoint pathway.